Financial Literacy and Planning on Financial Well-Being: The Mediating Role of Behavior - Sri Anah; Wahyu Anggraini; Abdul Rahmat; Garin Pratiwi Solihati (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
Financial well-being reflects employees’ ability to manage financial resources and maintain long-term stability. This quantitative study examines the effects of financial literacy, self-control, and financial planning on employees’ financial well-being, involving financial behavior as a mediating variable. Data were collected from 120 employees of PT SUAI through online and offline questionnaires and analyzed using SEM-PLS. The results show that financial literacy, self-control, and financial planning significantly influence financial behavior, which in turn positively and significantly affects financial well-being. However, only financial planning has a significant indirect effect on financial well-being through financial behavior, whereas financial literacy and self-control do not show significant mediation effects. These findings indicate that structured financial planning plays a key role in shaping consistent financial behavior that enhances financial well-being. Theoretically, the results support the Financial Management Behavior Theory and Financial Capability Framework, signifying the importance of behavioral implementation. Additionally, the study findings have crucial practical implications for organizations to prioritize applied financial education programs that focus on budgeting, saving, and long-term planning.